The function and expansion of the Patched- and Hedgehog-related homologs in C. elegans - Zugasti, Olivier; Rajan, Jeena; Kuwabara, Patricia E.

(untitled) (Genome Research, 2005)
The Hedgehog (Hh) signaling pathway promotes pattern formation and cell proliferation in Drosophila and vertebrates. Hh is a ligand that binds and represses the Patched (Ptc) receptor and thereby releases the latent activity of the multipass membrane protein Smoothened (Smo), which is essential for transducing the Hh signal. In Caenorhabditis elegans, the Hh signaling pathway has undergone considerable divergence. Surprisingly, obvious Smo and Hh homologs are absent whereas PTC, PTC-related (PTR), and a large family of nematode Hh-related (Hh-r) proteins are present. We find that the number of PTC-related and Hh-r proteins has expanded in C. elegans, and that this expansion occurred early in Nematoda. Moreover, the function of these proteins appears to be conserved in Caenorhabditis briggsae. Given our present understanding of the Hh signaling pathway, the absence of Hh and Smo raises many questions about the evolution and the function of the PTC, PTR, and Hh-r proteins in C. elegans. To gain insights into their roles, we performed a global survey of the phenotypes produced by RNA-mediated interference (RNAi). Our study reveals that these genes do not require Smo for activity and that they function in multiple aspects of C. elegans development, including molting, cytokinesis, growth, and pattern formation. Moreover, a subset of the PTC, PTR, and Hh-r proteins have the same RNAi phenotypes, indicating that they have the potential to participate in the same processes.